Pharmacokinetic evaluation and in vivo anti-inflammatory potential of cyanoacetate derivatives of succinimide - Aini Pervaiz; Muhammad Saeed Jan; Ali Khan; Bushra Ansari; Imad Ahmad; Wadood Ali Shah; Syed Muhammad Mukarram Shah; Abdur Rauf; Abdullah S. M. Aljohani; Waleed Al Abdulmonem; Marcello Iriti (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
The purpose of the study is to evalute the in vivo anti -inflammatory activity of newly synthesized cyanoacetate derivatives of succinimides (C-23, C-31, and C-44) and to elucidate their possible mechanisms of action through key inflammatory mediator pathways. Anti-inflammatory activity was assessed using carrageenan-induced paw oedema and arachidonic acid-induced ear oedema models in vivo. Mechanistic involvement was investigated through histamine-, prostaglandin-, leukotriene-, and bradykinin-induced paw oedema assays. In silico ADME studies were performed to predict pharmacokinetic properties and metabolic interactions. All tested compounds exhibited significant anti-inflammatory activity, with C-44 showing the highest potency. Mechanistic studies indicated that the anti-inflammatory effects were predominantly mediated via inhibition of prostaglandin and leukotriene pathways. ADME predictions suggested high gastrointestinal absorption, favourable oral bioavailability, and minimal interaction with major metabolic enzymes. The synthesized cyanoacetate derivatives, particularly C-44, demonstrate promising anti-inflammatory potential with favourable pharmacokinetic profiles, supporting their candidacy for further development as effective anti-inflammatory agents.